Selection of Effective Column Configuration in Nahdlatul Ulama University Flat in Kalimantan Barat Province - Vonia, Teresa; Yusuf, M.; Lestyowati, Yoke (Jurnal Teknik Sipil, 2024)
This study analyzes the structural performance of square, rectangular, and circular columns in the Nahdlatul Ulama University Flat (UNU Flat), Kubu Raya, West Kalimantan. Data included structural designs, seismic analysis, and specifications. Using interaction diagrams, square columns (400 x 400 mm, 12D16) demonstrated sufficient axial and bending load capacities, handling up to 2,500 kN and 200 kNm. Replacing them with circular columns (300 mm diameter) reduced the cross-sectional area but maintained safety. Rectangular columns (400 x 550 mm, 14D16) also showed strong load resistance with safe interaction points. Substituting these with circular columns (500 mm diameter) preserved structural safety. All column configurations met load and safety requirements, with circular columns offering potential material efficiency and more straightforward construction. The results confirm stability and strength under varying loads, emphasizing the feasibility of circular columns for optimized performance.